Obrazovatel'nyi komponent kak stimul dol'govremennoi fizkul'turno-sportivnoi deyatel'nosti obuchaemykh v sektsiyakh sportivnoi bor'by - Boltikov, Yu. V.; Solomakhin, O. B. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The significant part of persons wishing to be engaged into sports activity is not motivated to the achievement of results, or into the consummation of prize-winning places, but to the mastering with the certain skills. In wrestling there is no qualifying requirement to the contents of a technical arsenal, as it is practised in demonstration exercises. It reduces the effect of an educational component, which is interested for a significant part of children. The absence of those ones promotes the outflow from the wrestling of the significant number of pupils.